A computational method using multiresolution for volumetric data integration - Akinlar, Mehmet Ali; Kurulay, Muhammet; Secer, Aydin; Celenk, Mehmet (SPRINGEROPEN, 2012)
In this paper, we present a new method for integration of 3-D medical data by utilizing the advantages of 3-D multiresolution analysis and techniques of variational calculus. We first express the data integration problem as a variational optimal control problem where we express the displacement field in terms of wavelet expansions and, secondly, we write the components of the displacement field in terms of wavelet coefficients. We solve this optimization problem with a blockwise descent algorithm. We demonstrate the registration of 3-D brain MR images in the size of 257x257x65 as an application of the present method. Experimental results indicate that the method can integrate 3-D MR images better than only variational or only wavelet-based methods.
Keywords: inverse problems; variational optimization; multiresolution; image integration; Mathematics